N2E4, a Monoclonal Antibody Targeting Neuropilin-2, Inhibits Tumor Growth and Metastasis in Pancreatic Ductal Adenocarcinoma via Suppressing FAK/Erk/HIF-1α Signaling - Wang, Li; Wang, Lanlan; Wang, Shengyu; Zhou, Zonglang; Liu, Zongjunlin; Xu, Peilan; Luo, Xian; Wu, Ting; Luo, Fanghong; Yan, Jianghua (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive malignancy with extremely limited treatment; the effective targeting strategy stays an urgent unmet need. Neuropilin-2 (NRP2), a multifunctional transmembrane non-tyrosine-kinase glycoprotein, enhances various signal transduction pathways to modulate cancer progression. However, the application value of NRP2 as a therapeutic target in pancreatic cancer is still unclear. Here, we detected the elevated NRP2 was associated with the poor prognosis of pancreas carcinoma. The mouse monoclonal antibody targeting NRP2 (N2E4) that could specifically bind to PDAC cells was developed. Moreover, N2E4 inhibits PDAC proliferation, migration, and invasion in vitro, and repressed growth and metastasis in vivo. Mechanistically, the effect of N2E4 was mainly related to the blocking of interaction between NRP2 with integrinβ1 to inhibit FAK/Erk/HIF-1a/VEGF signaling. Therefore, N2E4 has the potential for targeting therapy of PDAC. This study lays a foundation for the future development of NRP2-based targeted therapy for PDAC.